Twenty-metre shuttle run: (mis)representation, (mis)interpretation and (mis)use - Armstrong, N.; Welsman, J. (British Journal of Sports Medicine, 2019)
Recent publications in the British Journal of Sports Medicine (BJSM) (mis)represent and (mis)interpret young people`s cardiorespiratory fitness (CRF) and potentially (mis)inform health promotion and clinical practice. 1 2 The papers recognise peak VO2as the criterion measure of CRF but base their estimations of peak VO2on performances in 20 m shuttle runs (20mSRT). Moreover, and of serious concern to us, estimated peak VO2is (mis)represented and (mis)interpreted in ratio with body mass (ie, in mL/kg/min).The papers identify a few of the limitations of shuttle running but a recent meta-analysis succinctly summarised the issues. It demonstrated that with children, over half of correlation coefficients between 20mSRT scores and peak VO2explain less than 50% of the variance in peak VO2. The meta-analysis reported that the criterion-related validity of the 20mSRT with children was only `moderate` and concluded, `testers must be aware that the performance score of the 20MSR test is simply estimation and not a direct measure of cardiorespiratory fitness`.3 An example of specious interpretation of 20mSRT scores is the assertion that …